2009
DOI: 10.1111/j.1365-2958.2009.06921.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Escherichia coli DNA polymerase I in chromosomal DNA replication fidelity

Abstract: SummaryWe have investigated the possible role of Escherichia coli DNA polymerase (Pol) I in chromosomal replication fidelity. This was done by substituting the chromosomal polA gene by the polAexo variant containing an inactivated 3Ј,5Ј exonuclease, which serves as a proofreader for this enzyme's misinsertion errors. Using this strain, activities of Pol I during DNA replication might be detectable as increases in the bacterial mutation rate. Using a series of defined lacZ reversion alleles in two orientations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 76 publications
(121 reference statements)
5
29
1
Order By: Relevance
“…Inactivation of the Pol I 3′ exonuclease causes a modest, 2–4 fold increase in specific lacZ reversion rates. This is apparent in an orientation-specific manner, confirming the expectation that Pol I errors arise primarily on the lagging strand (177). In this study, deficiency in the 3′ exonuclease of Pol I did not strongly enhance the mutator phenotype conferred by defects in the Polymerase III holoenzyme, suggesting that Pol I does not readily replace Pol III in the processing of misincorporation errors.…”
Section: E Coli Exonucleases: Properties Structure and Functionsupporting
confidence: 77%
“…Inactivation of the Pol I 3′ exonuclease causes a modest, 2–4 fold increase in specific lacZ reversion rates. This is apparent in an orientation-specific manner, confirming the expectation that Pol I errors arise primarily on the lagging strand (177). In this study, deficiency in the 3′ exonuclease of Pol I did not strongly enhance the mutator phenotype conferred by defects in the Polymerase III holoenzyme, suggesting that Pol I does not readily replace Pol III in the processing of misincorporation errors.…”
Section: E Coli Exonucleases: Properties Structure and Functionsupporting
confidence: 77%
“…The mutant frequencies Ϯ SE values were as follows: The fidelity mechanism. We have suggested that the dnaX36 mutator effect is most productively interpreted in terms of a defect in the processing of terminal mismatches (misinsertion errors) produced by the Pol III ␣-subunit (1,12,18,22,23). The current data on chromosomal DNA synthesis support this proposal.…”
Section: ϫ8supporting
confidence: 76%
“…Consistent with previous observations (1,5,18,22,23), the mutant frequencies for each of the lac alleles in control (dnaX ϩ ) strains are consistently higher for leading-strand replication than for lagging-strand replication. This persistent bias is the basis for our contention that on the E. coli chromosome, lagging-strand replication is more accurate.…”
supporting
confidence: 78%
“…The combination of these activities predetermines pol I to be a key component of the E. coli replication machinery by playing an essential role during Okazaki fragment processing [21], and fulfilling functions that in eukaryotes requires the coordinated action of two enzymes, pol δ and FEN1. By means of its 5′→3′ exonuclease activity, pol I removes RNA primers that are used to initiate Okazaki fragment synthesis, while via strand displacement DNA synthesis and 3′→5′ proofreading, it accurately fills the resulting gaps in the lagging strand [22]. …”
Section: Introductionmentioning
confidence: 99%